Separation of branched hexane isomers on zeolite BETA - Patrick, Bárcia (2006)
An adsorption study of sinle and binary soprtion of hexane isomers was performed covering a temperature range between 323 and 423 K.The effect of temperature and pressure in the shape of breakthrough curves was adressed.The IAST using DSL gibe a good prediction of multicomponent adsorption data.